2020
DOI: 10.1155/2020/4985693
|View full text |Cite
|
Sign up to set email alerts
|

Is Unfavourable Cervix prior to Labor Induction Risk for Adverse Obstetrical Outcome in Time of Universal Ripening Agents Usage? Single Center Retrospective Observational Study

Abstract: Cervical assessment on the Bishop scale prior to induction of labor (IOL) is one of the strongest prognostic criteria in relation to the success of the procedure. The commonly used preinduction methods are mainly aimed at reducing the percentage of cesarean sections. Our study has analyzed obstetric results of patients who had unripe cervix (Bishop score <7) before IOL and used preinduction (Foley catheter or misoprostol vaginal insert releasing 7 mcg of misoprostol per hour for 24 hours) with obstetric res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Physiologically, the cervix undergoes a ripening before delivery, which is associated with shortening, softening, changing the utero-cervical angle and opening the cervix. The Bishop score (BS) is commonly used in clinical examination to assess the cervix before delivery, which allows us to evaluate the chance of successful induction of labour 3 , 4 . Higher BS score before starting the IOL has strong negative correlation with the duration of the induction procedure (r = − 0.59 p < 0.01) 5 which may increase the patient's satisfaction with the IOL 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, the cervix undergoes a ripening before delivery, which is associated with shortening, softening, changing the utero-cervical angle and opening the cervix. The Bishop score (BS) is commonly used in clinical examination to assess the cervix before delivery, which allows us to evaluate the chance of successful induction of labour 3 , 4 . Higher BS score before starting the IOL has strong negative correlation with the duration of the induction procedure (r = − 0.59 p < 0.01) 5 which may increase the patient's satisfaction with the IOL 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the study cited above [12], the proportion of plurigravidas to the primagravidas in the studied group (31/69 = 0.45) was higher, and in our studies it was lower (24/111 = 0.21), (p = 0.018). Numerous studies show that vaginal childbirth in the history is one of the strongest predictive factors of induction efficiency and occurs in most of the predictive models published in the literature [14,15]. In our opinion, this proportion is crucial if we want to compare the percentage of caesarean sections between individual studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our first analysis, we found that patients with a higher initial Bishop score had a better response to the protocol, but after our multivariable analysis we did not find this variable to be a factor of good response, which seems surprising because every IOL is more effective on a ripe cervix [ 22 ].…”
Section: Discussionmentioning
confidence: 99%